ANALYSIS OF FOREIGN EXPERIENCE OF INTRODUCTION OF THE SCHOOL DRESS CODE - O, I, Denisova (Образование и наука, 2016)
The aim of this article is to analyze the international discourse on policy issues of school dress code; to identify problems relevant to the national system of education, and proposed ways of their solution.Methods. The methods involve summarizing of the content of the leading internationalsources regarding issues regarding school education and health; a systematic analysis of sociological researchResults. The polemic aspects to the requirements for the appearance of the students are considered. These requirements affect many important aspects and the principles of functioning of an educational system and all society in general: the observance of the constitutional rights of a child, including freedom of expression on grounds of gender; tolerance policy of intra school and state policy in the light of migration processes; problems of leveling of social and economic stratification of children, etc. The advantages and disadvantages of existing approaches to the development requirements in the countries of Europe, Asia, Africa, and North America are analysed.Scientific novelty. The influence of policy of a school dress-code on children’s behavior and health, relationships in multinational school groups, identification and safety of school students is proved. The ambiguity of information expressiveness and  ignificance of garments of clothing and other elements of appearance of modern school students is disclosed: symbols of belonging to a religious and/or national culture, a well-known fashion brand, a modern informal/political trend, as well as the severity of gender differences in the design of school uniforms. The correlation between the wording of the requirements of the dress code and the effectiveness of its implementation from the point of view of minimization of internal stresses in the school team is defined.Practical significance. Based on the systemized proposals for quality improvement of the socio-cultural environment of educational institutions, it will be possible to improve the efficiency of interaction of participants of an educational process